Transient, Biocompatible Electronics and Energy Harvesters Based on ZnO. Issue 20 (19th April 2013) - Dagdeviren, Canan; Hwang, Suk‐Won; Su, Yewang; Kim, Stanley; Cheng, Huanyu; Gur, Onur; Haney, Ryan; Omenetto, Fiorenzo G.; Huang, Yonggang; Rogers, John A.
<x xml:space="preserve">Abstract</x> The combined use of ZnO, Mg, MgO, and silk provides routes to classes of thin‐film transistors and mechanical energy harvesters that are soluble in water and biofluids. Experimental and theoretical studies of the operational aspects and dissolution properties of this type of transient electronics technology illustrate its various capabilities. Application opportunities range from resorbable biomedical implants, to environmentally dissolvable sensors, and degradable consumer electronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>